An Extension of Physical Optics Approximation for Dielectric Wedge Diffraction for a TM-Polarized Plane Wave - Nguyen, Duc Minh; Shirai, Hiroshi; Kim, Se-Yun (Oxford University Press, 2024)
In this study, the edge diffraction of a TM -polarized electromagnetic plane wave by two-dimensional dielectric wedges has been analyzed. An asymptotic solution for the radiation field has been derived from equivalent electric and magnetic currents which can be determined by the geometrical optics (GO) rays. This method may be regarded as an extended version of physical optics (PO). The diffracted field has been represented in terms of cotangent functions whose singularity behaviors are closely related to GO shadow boundaries. Numerical calculations are performed to compare the results with those by other reference solutions, such as the hidden rays of diffraction (HRD) and a numerical finite -difference time -domain (FDTD) simulation. Comparisons of the diffraction effect among these results have been made to propose additional lateral waves in the denser media.